Urgensitas Missions And Mission Bagi Kehidupan Bergereja - Bani, Yulianus; Bin Liwat, Delfian; Zai, Vinus (Jurnal Teologi (JUTEOLOG), 2025)
A common problem in church life is the issue of missions and mission, which should be the foundation and purpose of the church, but in reality, these missions and missions often encounter obstacles. This study uses a naturalistic paradigm with a modified qualitative approach, to suit theological research. Data collection and analysis techniques were carried out through interviews and observations. The findings of this study indicate a lack of understanding of missions and mission, a weak understanding of the purpose of church life, and a lack of understanding of the urgency of missions and mission for church life today. The church understands the importance of the role of missions and missions for the existence of the church. Church leaders do not give full attention to missions and evangelism. The church still has a shallow understanding of missions and church life, which is passive and work life is exclusive.